Extraction of the Proximal Phalanx: A New Option in Surgical Treatment of the Crossover Second Toe - Željko Jeleč; Tomislav Gjurašin; Ana Vuković Pirkl; Gordan Rujevčan (Case Reports in Orthopedics)
One of the biggest and commonest problems that is seen and treated by foot and ankle surgeons is the deformity where the second toe crosses over the hallux. According to available literature, this is the first published case of extraction of the proximal phalanx due to crossover toe deformity. We present the case of a 64-year-old Caucasian female with a crossover second toe deformity of her left foot. Because of this deformity, she was completely disabled to wear normal shoes and she felt intensive pain in her front part of the foot. She underwent a total extraction of the proximal phalanx of the second toe. After the operation, she was very satisfied with the status of the operated foot and the final result of the surgical treatment. The procedure that we performed could be a good possibility for the treatment of crossover second toe deformity because we got a good functional and cosmetic result, the morbidity associated with more advanced reconstruction is avoided, and the rehabilitation period was short. Patient satisfaction was high, and complications were minimal.